2023
DOI: 10.1055/a-2009-9945
|View full text |Cite
|
Sign up to set email alerts
|

Myxosarkom in der Halsregion eines Teddy-Hamsters (Mesocricetus auratus)

Abstract: ZusammenfassungDieses Fallbeispiel zeigt ein bisher selten beschriebenes Myxosarkom in der ventrolateralen Halsregion eines 1-jährigen Teddy-Hamsters. Die zytologische Beurteilung eines Feinnadelaspirats aus der Umfangsvermehrung zeigte zahlreiche pleomorphe Spindelzellen, die in hohen Mengen in einer muzinösen Matrix gelegen waren. Zytologisch wurde aufgrund der ausgeprägten Malignitätskriterien der Spindelzell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…It is also characterized by many atypical and pleomorphic cells, ranging from round to spindle or starshaped, with large nuclei, sometimes multiple, and atypical mitoses. 9 Thus, the cytologic characteristics in this report align with those described by Khachatryan et al, who diagnosed myxosarcoma in the ventral aspect of the spinous process of T6 of a dog. 10 Additionally, cutaneous myxosarcomas may have a high rate of metastasis to local lymph nodes, 1 as observed in this study, where metastasis was confirmed in the lymph nodes near the lesion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is also characterized by many atypical and pleomorphic cells, ranging from round to spindle or starshaped, with large nuclei, sometimes multiple, and atypical mitoses. 9 Thus, the cytologic characteristics in this report align with those described by Khachatryan et al, who diagnosed myxosarcoma in the ventral aspect of the spinous process of T6 of a dog. 10 Additionally, cutaneous myxosarcomas may have a high rate of metastasis to local lymph nodes, 1 as observed in this study, where metastasis was confirmed in the lymph nodes near the lesion.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding cytology, myxosarcoma is characterized by a slide background containing an intercellular matrix with eosinophilic and granular amorphous material. It is also characterized by many atypical and pleomorphic cells, ranging from round to spindle or star‐shaped, with large nuclei, sometimes multiple, and atypical mitoses 9 . Thus, the cytologic characteristics in this report align with those described by Khachatryan et al, who diagnosed myxosarcoma in the ventral aspect of the spinous process of T6 of a dog 10 .…”
Section: Discussionsupporting
confidence: 87%